Answer:
answer of your questions
Step-by-step explanation:
The process of obtaining the equation is similar, but it is more algebraically intensive. Given the focus (h,k) and the directrix y=mx+b, the equation for a parabola is (y - mx - b)^2 / (m^2 +1) = (x - h)^2 + (y - k)^2.
Yeah i will dude or dudet ask away
Answer:
y = 4(x+6)(x-2)
Step-by-step explanation:
y = 4x² + 16x - 48, factor out the 4
y = 4(x² + 4x - 12), find factors of 12
Factors of 12:
1*12, 2*6, 3*4; find a pair that sums to 4x or 4
6-2 = 4, since 12 is a negative number, a number in the factor must be negative, in this case, making 2 negative, would make 6-2 = 4
y = 4(x+6)(x-2)